Training of Choreographers in Higher Education Institutions - Androshchuk, Liudmyla; Medvid, Tetiana; Blahova, Tetiana; Zhyrov, Oleksandr; Bykova, Olha (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2023)
The relevance of the study is determined by the active development of the pedagogical art branches, where the professional competence development of future choreographers and the development of their creative views becomes the main aspect of specialists training in higher education institution and involves the creation of the necessary conditions on the way to their creative growth and professionalism. In this regard, the purpose of the research work is to determine the features of the training of choreographers in higher education institution, their professional development in the context of educational activities, the professional competence development in the process of practical professional training, as well as to determine possible ways to overcome the professional crisis and destruction. The basis of the theoretical and methodological approach in this article is a qualitative combination of system analysis methods of choreographer training in higher education institutions with an analytical study of the professional competence development of future specialists in the art of dancing, where the use of modern approaches involves the use of innovative forms and means of learning to implement the educational concept regarding the professional development of choreographers. The article presents the results that reflect the problem of implementing the training of choreographers in higher education institution on the way to the professional qualities development of future specialists, their motivation for self-education, the development of creative abilities and creativity, as well as the necessary skills development for future productive professional activity. The obtained results of the research work are of practical value for educators of higher education institutions that train the specialists in the art of dancing, for the perspective of introducing and implementing the latest training approaches in the educational process, as well as for practical purposes for determining the development of professional qualities of future choreographers in higher education institutions.